In vitro and in vivo analysis of antimicrobial agents alone and in combination against multi-drug resistant Acinetobacter baumannii - HE, Songzhe; HE, Hui; CHEN, Yi; CHEN, Yueming; WANG, Wei; YU, Daojun (Frontiers in Microbiology, 2015)
Objective To investigate the in vitro and in vivo antibacterial activities of tigecycline and other 13 common antimicrobial agents, alone or in combination, against multi-drug resistant Acinetobacter baumannii. Methods An in vitro susceptibility test of 101 Acinetobacter baumannii was used to detect minimal inhibitory concentrations (MICs). A mouse lung infection model of multi-drug resistant Acinetobacter baumannii,established by the ultrasonic atomization method, was used to define in vivo antimicrobial activities. Results Multi-drug resistant Acinetobacter baumannii showed high sensitivity to tigecycline (98% inhibition), polymyxin B (78.2% inhibition), and minocycline (74.2% inhibition). However, the use of these antimicrobial agents in combination with other antimicrobial agents produced synergistic or additive effects. In vivo data showed that white blood cell (WBC) counts in drug combination groups C (minocycline + amikacin) and D (minocycline + rifampicin) were significantly higher than in groups A (tigecycline) and B (polymyxin B) (P < 0.05), after administration of the drugs 24h post-infection. Lung tissue inflammation gradually increased in the model group during the first 24h after ultrasonic atomization infection; vasodilation, congestion with hemorrhage were observed 48h post infection. After three days of anti-infective therapy in groups A, B, C and D, lung tissue inflammation in each group gradually recovered with clear structures. The mortality rates in drug combination groups (groups C and D) were much lower than in groups A and B. Conclusion The combination of minocycline with either rifampicin or amikacin is more effective against multidrug-resistant Acinetobacter baumannii than single-agent tigecycline or polymyxin B. In addition, the mouse lung infection by ultrasonic atomization is a suitable model for drug screening and analysis of infection mechanism.